Dynamic evaporation of droplet with adjuvants under different environment conditions - Wang, Zhichong; Lan, Luchen; He, Xiongkui; Herbst, Andreas (International Journal of Agricultural and Biological Engineering, 2020)
Pesticide droplet is evaporating during the falling from the nozzle to the target. This dynamic evaporation is influenced by ambient temperature, relative humidity (RH), adjuvant type and concentration. In the evaporation process, the droplet size at different height is affected by the droplet evaporation. Based on this, this study determined the droplet dynamic evaporation by collecting the droplets from different height via silicone oil method with a certain temperature and RH. Eight adjuvants were chosen, including three organo-silicon, three vegetable oil and two non-ionic, with five concentrations. All droplets were generated by a droplet generator. The results showed that the type of adjuvant, ambient temperature and RH had no significant influence on droplet size generated by droplet generator. All the adjuvants in this experiment cannot reduce dynamic evaporation; Concentration of adjuvant made a difference in dynamic evaporation. This could be because of the property of adjuvant. Organo-silicon adjuvants have a negative correlation with water vapor pressure, it showed less dynamic evaporation at high temperature and RH. Vegetable oil and non-ionic adjuvant, they are the same as the controlled blank that the dynamic evaporation reduces with decreasing temperature and increasing RH. Keywords: pesticide droplet, dynamic evaporation, adjuvant, temperature, relative humidity DOI: 10.25165/j.ijabe.20201302.5353 Citation: Wang Z C, Lan L C, He X K, Herbst A. Dynamic evaporation of droplet with adjuvants under different environment conditions. Int J Agric & Biol Eng, 2020; 13(2): 1–6.